هيئات وسلطات الضبط الإداري بين المركزية والمحلية في الجزائر - • برة نعيمة بوعكاز رابح (جامعة المسيلة, 2022)
يعد الضبط الإداري من الوظائف المهمة والساسة للدولة ويظهر ذلك بشكل خص في الظروف الاستثنائية وخاصة عندما يمس تهديد عناصر الضبط (النظام العام، الصحة العمومية، الآداب العامة). ونظمت القوانين الجزائرية سلطات وهيئات الضبط الإداري إلى هيئات مركزية وأخرى محلية تمارس كل اختصاصاتها وفقا لمراكزها القانونية والقوانين الناظمة. والضبط الإداري وطنيا نجده فيما يقوم به رئيس الجمهورية والوزير الأول والوزراء، أما محليا فنلمسه في صلاحيات ومهام الوالي ورئيس المجلس الشعبي البلدي. وقد وضعت جملة من الآليات كرسها المشرع الجزائري بعناية في المنظومة القانونية لتمكن سلطات وهيئات الضبط الإداري من ممارسة وظيفتها في إطار القانون واحترام مبدأ المشروعية وحفاظا على الحقوق والحريات. الكلمات المفتاحية: الضبط الإداري، الهيئات المركزية، الهيئات المحلية، مبدأ المشروعية، التشريع الجزائري. Abstract: Administrative control is one of the important and political functions of the state and this appears especially in exceptional circumstances, especially when the threat to the elements of control (public order, public health, public morals) affects. Algerian laws have organized the administrative control authorities and bodies into central and local bodies that exercise all their competencies in accordance with their legal positions and the regulating laws. Nationally, we find administrative control in what the President of the Republic, the Prime Minister, and the ministers do. Locally, we see it in the powers and tasks of the governor and the president of the Municipal People’s Council. A number of mechanisms have been carefully established by the Algerian legislator in the legal system to enable the administrative control authorities and bodies to exercise their function within the framework of the law, respect the principle of legality, and preserve rights and freedoms. Keywords: administrative control, central bodies, local bodies, the principle of legality, Algerian legislation.
Keywords: الضبط الإداري، الهيئات المركزية، الهيئات المحلية، مبدأ المشروعية، التشريع الجزائري